Using Information and Communication Technologies in Teaching the Mother Tongue in the Higher Educational Institutions - Buzulaykho Turgunovna Kodirova, Feruza Makhammatkosimovna Kuchkarova, Khojiakbar Zafarjon-ugli Mukhammadjonov (International Journal of Advanced Science and Technology, 2020)
This article was written with the aim of theoretically substantiating the pedagogical feasibility of realizing the capabilities of ICT tools in the classroom of the native language and preparing future teachers of the mother tongue using ICT tools in their professional activities. The following tasks were identified and solved: to analyze the state of ICT use in the work of mother tongue teachers in universities; to identify the pedagogical goals of using ICT tools in the process of teaching the mother tongue in a personality-oriented approach; to determine the requirements for the structure, content of educational material and the organization of educational activities using ICT tools in the lessons of the native language; to develop and experimentally verify the effectiveness of pedagogical conditions for using ICT tools in improving the quality of teaching the mother tongue at a university.